Świat metafor owadzich w Dziennikach czasu wojny Zofii Nałkowskiej - Krupiński, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The main aim of the article is an analysis of entomological motifs in the Nałkowska’s wartime diary. The surprising frequency of these motifs gives an opportunity for a more general discussion: the key context for an explanation of insect metaphors seems to be the tendency, common for modernist authors, to place the concept of humanity in a widely understood philosophy of nature. The rule would also apply for the war, or more generally, for mechanisms of human violence, which Nałkowska subjects in her diary to a peculiar darwinistic representation. Understanding the war as a “naturalistic fact” (Hanna Kirchner’s description) results in a gradual blurring of the differences between the violence of nature and the violence of history. The author of the article has identified a similar procedure in Czesław Miłosz’s work, which constitutes a specific counterpoint for Nałkowska’s wartime diary.